Trends and predictors of myocardial infarction or vascular death after ischaemic stroke or TIA in China, 2007–2018: insights from China National Stroke Registries. Issue 2 (30th October 2020) - Li, Long; Pan, Yuesong; Wang, Mengxing; Jing, Jing; Meng, Xia; Jiang, Yong; Guo, Caixia; Jin, Zening; Wang, Yongjun
Abstract : Background: Although stroke management, primary and secondary preventions have been improved in China last decades, the trends and predictors of major vascular events after ischaemic stroke or transient ischaemic attack (TIA) at national scale are less known. Methods: Data were obtained from the three phases of China National Stroke Registry (CNSR), including CNSR-Ⅰ (years 2007–2008), CNSR-Ⅱ (years 2012–2013) and CNSR-III (years 2015–2018). For comparison, patients who were diagnosed as ischaemic stroke or TIA were included. Kaplan-Meier estimates of myocardial infarction (MI) or vascular death were calculated at 1 year. Independent predictors were further assessed with a Cox proportional hazards regression. Results: From 2007 to 2018, a total of 50 284 patients with ischaemic stroke or TIA were enrolled in this study. A declining trend was found in 1-year MI or vascular death (p for trend <0.001), while recurrent stroke depicted a U-shape curve with a nadir in 2012–2013 cohort. A similar trend was also observed in patients who were admitted to 26 hospitals in all three CNSRs. In 2015–2018 cohort, only 251 (1.7%; 95% CI 1.5% to 1.9%) MI or vascular death had occurred at 1 year. Older age, previous stroke or TIA, history of coronary artery disease and the National Institutes of Health Stroke Scale >6 were associated with both an increased risk of MI or vascular death and recurrent stroke. While early antiplatelet therapy and lipid-lowering agents at discharge predicted a reduced risk. Conclusion: A declining trend and current low incidence of MI or vascular death, rather than recurrent stroke, after ischaemic stroke or TIA were observed in China. Traditional factors were found as independent predictors. These findings suggested there is still much room to improve for stroke management.